The Paley's concept of liberty and the eclipse of the republicanism - Picoli, Rogério Antônio (Cadernos de Ética e Filosofia Política, 2013)
According to Pettit and Skinner the rising of utilitarianism would havedecisively contributed tothe eclipseof themodernrepublican tradition. The Utilitarianswould have beenresponsible for aradical critique of theconcept ofrepublican liberty, which would have resultedin the predominanceof theHobbesianconception of freedom. The sharpnessand strengthof the utilitarian attackto theconception ofrepublican libertywould have besummarized in aset ofobjectionsformulated,in the lateeighteenth century, by theEnglishtheological utilitarianWilliamPaley. Anexaminationof Paley’sthought showsthathis conception of liberty,contrary to whatsuggestSkinner andPettit, is quite distinct from theHobbesian concept.